Healing in the Gospel of Matthew : reflections on method and ministry - Wilson, Walter T. (Fortress Press, 2014)
Although healing constitutes both a major theme of biblical literature and a significant practice of biblical communities, healing themes and experiences are not always conspicuous in presentations of biblical theology. Walter T. Wilson adopts an interdisciplinary approach to the healing narratives in the Gospel of Matthew, combining the familiar methods of form, redaction, and narrative criticisms with insights culled from medical anthropology, feminist theory, disability studies, and ancient archaeology. His focus is the New Testament's longest and most systematic account of healing, Matthew chapters 8 and 9, which he investigates by situating the text within a broad range of ancient healing traditions. The close exegetical readings of each healing narrative culminate in a final synthesis that pulls together what can be said about Matthew's understanding of healing, how Matthew's narratives of healing expose the distinctive priorities of the evangelist, and how these priorities relate to the theology of the Gospel as a whole.